The energy and lifetime of resonant states with real basis sets - Cuestas, María Eloisa (2013)
Using a probabilistic interpretation of resonant states and square-integrable real basis set expansion techniques, we propose a formula useful to calculate the lifetime of a resonance. Our approach does not require an estimation of the density of states. The method is illustrated with calculations of s- and p-resonant state energies and lifetimes.